Peranan Pramuwisata Dan Pemerintah Dalam Mencegah Pelecehan Kepariwisataan Budaya Bali - A. A. Istri Eka Krisna Yanti (Kertha Wicaksana, 2020)
Bali is one of the most popular tourist destinations in the world. The tourism model that is developed in Bali is Bali Cultural Tourism which is based on the philosophy of Tri Hita Karana which is the source of the teachings of Hinduism. The rise of the phenomenon of illegal guides who are not certified in explaining the uniqueness of Bali's Cultural Tourism, has implications for the harassment of Balinese culture into the background of the writing of this study. This study focuses on examining the role of guides and government in preventing harassment of the Bali Cultural Tourism. In this research, there are two problem formulations studied; what are the competency certification procedures of guides in the Province of Bali and how is the supervision of the Government Guide in the Province of Bali. The research method used in this study is a normative research method with a focus on studying the legislation and literature relevant to the research topic. Based on the provisions of Article 15 of the Bali Province Regulation Number 5 Year 2016 Regarding Tour Guides, it is known that the authority of guide supervision is owned by the Governor of Bali Province which is carried out by the department. However, the provisions of Article 15 (5) of Regional Regulation of the Province of Bali Number 5 of 2016 concerning Guides mentioned that the Governor of the Province of Bali formed a team of guides to carry out supervision of guides. Furthermore, Bali Provincial Regulation Number 5 Year 2016 About Guides does not explain further the work mechanism of the supervisory team, therefore the government needs to form more stringent regulations relating to the supervision of guides to maintain the image of Bali's Cultural Tourism and provide legal protection to Certified tour guide in Bali Province.